An evaluation of the thermoregulatory potential of in ovo delivered bioactive substances (probiotic, folic acid, and essential oil) in broiler chickens - Oladokun, Samson; Dridi, Sami; Adewole, Deborah (Poultry science, 2023)
Mitigating the negative effects of heat stress (HS) is a critical challenge for the global poultry industry. This study evaluated the thermoregulatory potential of 3 in ovo delivered bioactive substances using selected gut health parameters. Eggs were incubated and allotted to 5 groups, and respective bioactive substances delivered. These groups included—the noninjected, in ovo saline, in ovo folic acid (FA), in ovo probiotics (P), and in ovo essential oil (EO). At hatch, chicks were assigned to 5 new posthatch treatment combinations, including A) Negative control (NC)—noninjected eggs offered a basal corn-wheat-soybean diet, B) Antibiotics—NC + 0.05% bacitracin methylene disalicylate, C) In ovo FA—eggs injected with FA + NC diet, D) In ovo probiotics—eggs injected with probiotics + NC diet, E) In ovo + in-water EO—eggs injected with EO and supplied EO via drinking water + NC diet. Birds were raised for 28 d in 8 replicate cages/treatment (6 birds/cage) and exposed to either a thermoneutral (24°C ± 0.2) or HS challenge (31°C) condition from d 21 to d 28. The in ovo delivered FA and EO treatments reduced (P < 0.001) hatchability by at least 26% compared to NC. Induced HS reduced (P < 0.001) total plasma protein, total antioxidant capacity, and villus width in the duodenum and jejunum. Independent of HS and compared to NC, the in ovo + in-water EO treatment resulted in (P < 0.05) at least a 15% increase in villus height: crypt depth across the 3 gut sections. The in ovo + in-water EO treatment also increased the relative mRNA expression of intestinal barrier-related genes (Claudin1,3,4, Occludin, Zona occludens-2, and Mucin 2). Under HS, the in ovo + in-water EO treatment recorded a 3.5-fold upregulation of amino acid transporter gene (SLC1A1), compared to NC. Subject to further hatchability optimization, the in ovo + in-water delivery of EO show potential to afford broiler chicken thermotolerance.